Spoilage pattern and shelf life characteristics of binagol - Barraza, Vera Leonora M.
ABSTRACT Binagol from Dagami, Leyte is one of the leading native delicacies in the province. It has a high marketability and one of the most in-demand pasalubong. Based on the mean values for the general acceptability of five binagol samples, the sample which came from Salazar got the highest mean. The average moisture content and water activity exhibited by the product were 32.59% and 0.86, respectively. These values showed that the product is an intermediate moisture food. Binagol exhibits a light brown to golden brown color. It has very distinct sweet flavor and aroma which are unique to the product. The sample also exhibits a smooth texture. Initial microbiological tests showed that the sample had a low yeast and mold count. The stability of binagol at room temperature was attributed to its low water activity and the type of processing employed. However, a marked change in the physico-chemical characteristics of the product was observed upon prolonged storage. After six days of storage, a high microbial count was exhibited in terms of total plate count, lactic acid bacteria and yeast and mold count. The presence of the mentioned microorganisms affected the physico-chemical characteristics of the sample. The sudden increase in the microbial count of the sample upon prolonged storage was attributed to the breakdown of the packaging material and the favorable conditions imparted by the environment and the sample's inherent characteristics. The spoilage of the product was also brought about by possible post-processing contamination. High quality binagol can be kept at room temperature for about three to five days since a marked increase in the physico-chemical and micrbiological changes are exhibited upon prolonged storage.